Optimizing The Financial Domain With Robotic Process Automation: Invoice Data Extraction - Andre Suryaningprang; Yoyo Sudaryo; Riyandi Nur Sumawidjaja; Andhika Mochamad Siddiq; Dedi Supiyadi (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The industrialization process has led to the automation of business processes with the goal of economic efficiency. This research was conducted at a trading company that requires an effective administrative process with time efficiency. So this need becomes a reason for the need for technology. Currently, a new technology has emerged that will revolutionize how humans work in companies, namely Robotic Process Automation.Purpose: This study focuses on first, proposing a model in the scope of financial domain, especially in invoice processing and reconciliation. Second, proposing an RPA solution using UI Path which can be used to improve invoice processing and reconciliation processes. Design: This study uses the Design Science Research (DSR) methodology, so that the research object is the framework of the design itself. There are several steps taken to build RPA, namely (1) Problem Analysis and Motivation, (2) Determining Solution Goals, (3) Designing and Developing Solutions (4) performance evaluation. From the research, the results show that RPA performance has met expectations in terms of: speed.Finding/ Result: The findings of this study indicate that there are limitations in implementation due to variations in invoice formats across different companies. As a result, there is a need for ongoing adjustments and regular updates to the system and hardware to accommodate changes in invoice formats and business processes of each company.Conclusion: According to the study's findings it was concluded that RPA model has a good performance and has already met the side's expectations in terms of speed.Originality/ value (state of the art): The use of Robotic Process Automation (RPA) in financial processes, notably invoice data extraction, is a cutting-edge technology that improves financial efficiency and accuracy. This study, conducted on an Indonesian trading organization, reveals how RPA may be used to streamline financial workflows by automating repetitive, time-consuming procedures, minimizing human error, and enhancing data management processes. Keywords: financial domain, robotic process automation, Design Science Research (DSR), data management, invoice formats